A graphene-based antistatic PC composite material and preparation method thereof

By preparing modified polycarbonate and modified filler, the problems of poor antistatic effect and low-temperature mechanical properties of PC composites are solved, and the combination of efficient antistatic and good mechanical properties is achieved.

CN119432093BActive Publication Date: 2025-04-08JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510035382.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

At this stage, PC composite materials have poor anti-static effects and low-temperature mechanical properties. Especially in the combination of graphene and commonly used thermoplastic polymers such as polycarbonate, poor interfacial bonding and graphene agglomeration problems lead to a decrease in conductivity.

Method used

By preparing modified polycarbonate and modified filler, react with materials such as dihydropolysiloxane, allyl glycidyl ether, aniline and zinc oxide to form a composite material with dynamic crosslinking and high flexibility. The modified filler enhances the grafting activity of graphene and improves the conductivity of composite materials by treating graphene oxide, ethylenediamine and hydrazine hydrate.

Benefits of technology

It realizes the efficient antistatic properties and good low-temperature mechanical properties of PC composite materials, enhances the tensile strength and bending properties of composite materials, and ensures the stability of conductive paths of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antistatic PC composite material based on graphene and a preparation method thereof. Modified polycarbonate, modified filler and zinc oxide are extruded to prepare the antistatic PC composite material. During the melt extrusion of the modified polycarbonate, the modified filler and the zinc oxide, under the action of zinc oxide, the maleimide group of the modified polycarbonate side chain can react with the furan group on the modified filler to form a dynamic crosslink in the composite material, thereby redistributing the load when subjected to stress, thereby increasing the mechanical strength and toughness of the composite material. Meanwhile, the composite material contains organic silicon segments, and the silicon-oxygen bonds have high flexibility, so that the molecular chains of the composite material can maintain a certain mobility at low temperatures. The molecular side chains also contain polyaniline segments, which can contact with the modified filler, thereby forming a stable conductive path in the composite material, thereby ensuring the antistatic effect of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PC composite material preparation, and in particular to a graphene-based antistatic PC composite material and a preparation method thereof. Background Art

[0002] With the multifunctionalization of plastic products and the high integration of electronic circuits, the application of materials with conductive properties is becoming more and more extensive. PC materials have high impact resistance, flame retardancy of up to V-2, and good weather resistance. They are widely used in electronic and electrical products. However, when plastics come into contact with devices carrying current or rub against other materials, they will carry static electricity, which will lead to static electricity accumulation and signal interference. This is not conducive to the application of plastic products in printers, home appliance housings, or signal line connectors. Graphene is a two-dimensional nanomaterial with good conductivity, high strength, and ultra-high surface area ratio. Its excellent performance makes it an ideal choice for the development of efficient antistatic materials. However, adding graphene to commonly used thermoplastic polymers such as polycarbonate faces the problems of poor interface bonding and graphene agglomeration. These problems will weaken the conductive properties of graphene and reduce the antistatic effect of composite materials. Summary of the invention

[0003] The purpose of the present invention is to provide an antistatic PC composite material based on graphene and a preparation method thereof, which solves the problem that the current PC composite material has poor antistatic effect and low low-temperature mechanical properties.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing an antistatic PC composite material based on graphene specifically comprises the following steps:

[0006] Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed uniformly, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 80-90° C. to obtain modified silicone;

[0007] Step A2: mixing modified organosilicon, aniline and DMF, reacting for 1-1.5 hours at a speed of 150-200 r / min, a temperature of 80-85° C. and a pH value of 11-12 to obtain a modified monomer, introducing nitrogen protection into the modified monomer, 1,4-cyclohexanedimethanol, diphenyl carbonate, lithium acetylacetonate and 4-methylaminopyridine, reacting for 2-3 hours at a temperature of 130-135° C., raising the temperature to 200-210° C., and reacting for 4-6 hours to obtain a pretreated polycarbonate;

[0008] Step A3: The pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and DMF are uniformly mixed, stirred and hydrochloric acid is added to a pH value of 1-2 at a speed of 150-200 r / min and a temperature of 80-90°C, and ammonium persulfate is added to react for 20-25 hours to obtain a modified polycarbonate, and the modified polycarbonate, modified filler and zinc oxide are added to a twin-screw extruder, and extruded and cooled at a speed of 80 r / min, a temperature of 240°C in the first zone, a temperature of 240°C in the second zone, a temperature of 245°C in the third zone, a temperature of 245°C in the fourth zone, a temperature of 245°C in the fifth zone and a temperature of 250°C in the sixth zone to obtain an antistatic PC composite material.

[0009] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A1 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and allyl alcohol glycidyl ether is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0010] Furthermore, the molar ratio of the modified silicone and aniline described in step A2 is 1:2, the molar ratio of the modified monomer, 1,4-cyclohexanedimethanol and diphenyl carbonate is 2.8:12:15, the amount of lithium acetylacetonate is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol, and the amount of 4-methylaminopyridine is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol.

[0011] Furthermore, the amount ratio of the pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and ammonium persulfate in step A3 is 20g:20mmol:2mmol:12mmol, and the mass ratio of the modified polycarbonate, the modified filler and zinc oxide is 100:20-30:1-3.

[0012] Further, the modified filler is prepared by the following steps:

[0013] Step B1: adding concentrated sulfuric acid to a reaction kettle, stirring and adding graphene and potassium permanganate at a speed of 800-1000 r / min and a temperature of 20-25° C., stirring for 3-4 hours, heating to 45-50° C., reacting for 3-5 hours, adding deionized water to terminate the reaction and washing to neutrality to obtain graphene oxide, mixing graphene oxide, ethylenediamine, dicyclohexylcarbodiimide and toluene, reacting for 2-3 hours at a speed of 200-300 r / min and a temperature of 25-30° C., to obtain modified graphene;

[0014] Step B2: Furoyl chloride, 2,2-dihydroxymethylbutyric acid, triethylamine and toluene are mixed, and the reaction is carried out for 3-5 hours at a rotation speed of 200-300 r / min and a temperature of 35-40°C, and the pH value is adjusted to be acidic to obtain an intermediate, and the modified graphene, the intermediate, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out for 2-3 hours at a rotation speed of 200-300 r / min and a temperature of 25-30°C to obtain a precursor, and the precursor is dispersed in deionized water, hydrazine hydrate is added, and the reaction is carried out for 20-25 hours at a rotation speed of 300-500 r / min and a temperature of 90-95°C to obtain a modified filler.

[0015] Furthermore, the dosage ratio of concentrated sulfuric acid, graphene and potassium permanganate in step B1 is 110mL:1g:6g, the mass fraction of concentrated sulfuric acid is 98%, and the molar ratio of carboxyl, ethylenediamine and dicyclohexylcarbodiimide on graphene oxide is 1:1:1.1.

[0016] Furthermore, the molar ratio of furanoyl chloride, 2,2-dihydroxymethylbutyric acid and triethylamine in step B2 is 2:1:3, the molar ratio of the amino group, the intermediate and dicyclohexylcarbodiimide on the modified graphene is 1:1:1.1, the amount ratio of the precursor, deionized water and hydrazine hydrate is 1g:1000mL:10mL, and the mass fraction of hydrazine hydrate is 80%.

[0017] Beneficial effects of the present invention: the graphene-based antistatic PC composite material disclosed by the present invention is prepared by ring-opening octamethylcyclotetrasiloxane as a raw material and polymerizing it with tetramethyldisiloxane to obtain dihydrogenpolysiloxane, reacting dihydrogenpolysiloxane with allyl alcohol glycidyl ether so that Si-H bonds on dihydrogenpolysiloxane react with double bonds on allyl alcohol glycidyl ether to obtain modified organic silicon, reacting the modified organic silicon with aniline so that epoxy groups on the organic silicon react with amino groups on the aniline to obtain modified monomers, exchanging esters and condensing the modified monomers, 1,4-cyclohexanedimethanol and diphenyl carbonate to obtain pretreated polycarbonate, forming polyaniline with the pretreated polycarbonate, aniline and N-(4-aminobenzene)maleimide under the action of ammonium persulfate and forming maleimide end-capping at the end points of the polyaniline to obtain modified polycarbonate, and extruding the modified polycarbonate, modified filler and zinc oxide to obtain the antistatic PC composite material.

[0018] The modified filler is prepared by oxidation treatment of graphene as a raw material to obtain graphene oxide, the graphene oxide is reacted with ethylenediamine so that the carboxyl group on the graphene oxide reacts with the amino group on the ethylenediamine, active amino groups are grafted to obtain modified graphene, furanoyl chloride is reacted with 2,2-dihydroxymethylbutyric acid so that the acyl chloride group on the furanoyl chloride reacts with the hydroxyl group on the 2,2-dihydroxymethylbutyric acid to obtain an intermediate, the modified graphene is reacted with the intermediate so that the amino group on the modified graphene reacts with the carboxyl group on the intermediate to obtain a precursor, and the precursor is treated with hydrated nitrile to obtain a modified filler.

[0019] During the melt extrusion of modified polycarbonate, modified filler and zinc oxide, under the action of zinc oxide, the maleimide group of the modified polycarbonate side chain can react with the furan group on the modified filler to form a DA reaction, thereby forming a dynamic crosslink in the composite material, and then redistributing the load when subjected to stress, thereby increasing the mechanical strength and toughness of the composite material. At the same time, the composite material contains organic silicon segments, and the silicon-oxygen bonds have high flexibility, so that the molecular chains of the composite material can maintain a certain mobility even at low temperatures. There are also polyaniline segments in the molecular side chains, and the polyaniline segments can contact with the modified filler, thereby forming a stable conductive path in the composite material, thereby ensuring the antistatic effect of the composite material. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Embodiment 1: A method for preparing an antistatic PC composite material based on graphene, comprising the following steps:

[0022] Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 3 hours at a speed of 120 r / min and a temperature of 105° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed uniformly, and the mixture is reacted for 3 hours at a speed of 150 r / min and a temperature of 80° C. to obtain modified silicone;

[0023] Step A2: Modified organosilicon, aniline and DMF are mixed, and reacted for 1 hour at a speed of 150 r / min, a temperature of 80° C. and a pH value of 11 to obtain a modified monomer, and the modified monomer, 1,4-cyclohexanedimethanol, diphenyl carbonate, lithium acetylacetonate and 4-methylaminopyridine are passed through nitrogen protection, and reacted for 2 hours at a temperature of 130° C., and then heated to 200° C. and reacted for 4 hours to obtain a pretreated polycarbonate;

[0024] Step A3: The pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and DMF are mixed uniformly, stirred and hydrochloric acid is added to a pH value of 1 at a speed of 150 r / min and a temperature of 80°C, and ammonium persulfate is added to react for 20 hours to obtain a modified polycarbonate. The modified polycarbonate, modified filler and zinc oxide are added to a twin-screw extruder, and extruded and cooled at a speed of 80 r / min, a temperature of 240°C in the first zone, a temperature of 240°C in the second zone, a temperature of 245°C in the third zone, a temperature of 245°C in the fourth zone, a temperature of 245°C in the fifth zone and a temperature of 250°C in the sixth zone to obtain an antistatic PC composite material.

[0025] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A1 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and allyl alcohol glycidyl ether is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0026] The molar ratio of the modified silicone and aniline described in step A2 is 1:2, the molar ratio of the modified monomer, 1,4-cyclohexanedimethanol and diphenyl carbonate is 2.8:12:15, the amount of lithium acetylacetonate is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol, and the amount of 4-methylaminopyridine is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol.

[0027] The amount ratio of the pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and ammonium persulfate described in step A3 is 20g:20mmol:2mmol:12mmol, and the mass ratio of the modified polycarbonate, the modified filler and zinc oxide is 100:20:1.

[0028] The modified filler is prepared by the following steps:

[0029] Step B1: adding concentrated sulfuric acid to a reactor, stirring and adding graphene and potassium permanganate at a speed of 800 r / min and a temperature of 20° C., stirring for 3 h, heating to 45° C., reacting for 3 h, adding deionized water to terminate the reaction and washing to neutrality to obtain graphene oxide, mixing graphene oxide, ethylenediamine, dicyclohexylcarbodiimide and toluene, reacting for 2 h at a speed of 200 r / min and a temperature of 25° C., to obtain modified graphene;

[0030] Step B2: Furoyl chloride, 2,2-dihydroxymethylbutyric acid, triethylamine and toluene are mixed, and the mixture is reacted at a speed of 200 r / min and a temperature of 35°C for 3 hours, and the pH value is adjusted to be acidic to obtain an intermediate. The modified graphene, the intermediate, dicyclohexylcarbodiimide and DMF are mixed, and the mixture is reacted at a speed of 200 r / min and a temperature of 25°C for 2 hours to obtain a precursor. The precursor is dispersed in deionized water, hydrazine hydrate is added, and the mixture is reacted at a speed of 300 r / min and a temperature of 90°C for 20 hours to obtain a modified filler.

[0031] The amount ratio of concentrated sulfuric acid, graphene and potassium permanganate described in step B1 is 110mL:1g:6g, the mass fraction of concentrated sulfuric acid is 98%, and the molar ratio of carboxyl, ethylenediamine and dicyclohexylcarbodiimide on graphene oxide is 1:1:1.1.

[0032] The molar ratio of furanoyl chloride, 2,2-dihydroxymethylbutyric acid and triethylamine described in step B2 is 2:1:3, the molar ratio of the amino group, the intermediate and dicyclohexylcarbodiimide on the modified graphene is 1:1:1.1, the amount ratio of the precursor, deionized water and hydrazine hydrate is 1g:1000mL:10mL, and the mass fraction of hydrazine hydrate is 80%.

[0033] Embodiment 2: A method for preparing an antistatic PC composite material based on graphene, comprising the following steps:

[0034] Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 4 hours at a speed of 120 r / min and a temperature of 110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed uniformly, and the mixture is reacted for 4 hours at a speed of 150 r / min and a temperature of 85° C. to obtain modified silicone;

[0035] Step A2: Modified organosilicon, aniline and DMF were mixed, and reacted for 1.5 hours at a speed of 150 r / min, a temperature of 85° C. and a pH value of 11 to obtain a modified monomer. The modified monomer, 1,4-cyclohexanedimethanol, diphenyl carbonate, lithium acetylacetonate and 4-methylaminopyridine were protected by nitrogen and reacted for 3 hours at a temperature of 130° C. The temperature was raised to 205° C. and reacted for 5 hours to obtain a pretreated polycarbonate;

[0036] Step A3: The pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and DMF are mixed uniformly, stirred and hydrochloric acid is added to a pH value of 2 at a speed of 150 r / min and a temperature of 85°C, and ammonium persulfate is added to react for 20 hours to obtain a modified polycarbonate. The modified polycarbonate, modified filler and zinc oxide are added to a twin-screw extruder, and extruded and cooled at a speed of 80 r / min, a temperature of 240°C in the first zone, a temperature of 240°C in the second zone, a temperature of 245°C in the third zone, a temperature of 245°C in the fourth zone, a temperature of 245°C in the fifth zone and a temperature of 250°C in the sixth zone to obtain an antistatic PC composite material.

[0037] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A1 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and allyl alcohol glycidyl ether is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0038] The molar ratio of the modified silicone and aniline described in step A2 is 1:2, the molar ratio of the modified monomer, 1,4-cyclohexanedimethanol and diphenyl carbonate is 2.8:12:15, the amount of lithium acetylacetonate is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol, and the amount of 4-methylaminopyridine is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol.

[0039] The amount ratio of the pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and ammonium persulfate described in step A3 is 20g:20mmol:2mmol:12mmol, and the mass ratio of the modified polycarbonate, the modified filler and zinc oxide is 100:25:2.

[0040] The modified filler is prepared by the following steps:

[0041] Step B1: adding concentrated sulfuric acid to a reactor, stirring and adding graphene and potassium permanganate at a speed of 800 r / min and a temperature of 25° C., stirring for 3.5 hours, heating to 48° C., reacting for 4 hours, adding deionized water to terminate the reaction and washing to neutrality to obtain graphene oxide, mixing graphene oxide, ethylenediamine, dicyclohexylcarbodiimide and toluene, reacting for 2 hours at a speed of 200 r / min and a temperature of 30° C., to obtain modified graphene;

[0042] Step B2: Furoyl chloride, 2,2-dihydroxymethylbutyric acid, triethylamine and toluene are mixed, and the mixture is reacted at a speed of 200 r / min and a temperature of 38°C for 4 hours, and the pH value is adjusted to be acidic to obtain an intermediate. The modified graphene, the intermediate, dicyclohexylcarbodiimide and DMF are mixed, and the mixture is reacted at a speed of 200 r / min and a temperature of 30°C for 2 hours to obtain a precursor. The precursor is dispersed in deionized water, hydrazine hydrate is added, and the mixture is reacted at a speed of 500 r / min and a temperature of 90°C for 25 hours to obtain a modified filler.

[0043] The amount ratio of concentrated sulfuric acid, graphene and potassium permanganate described in step B1 is 110mL:1g:6g, the mass fraction of concentrated sulfuric acid is 98%, and the molar ratio of carboxyl, ethylenediamine and dicyclohexylcarbodiimide on graphene oxide is 1:1:1.1.

[0044] The molar ratio of furanoyl chloride, 2,2-dihydroxymethylbutyric acid and triethylamine described in step B2 is 2:1:3, the molar ratio of the amino group, the intermediate and dicyclohexylcarbodiimide on the modified graphene is 1:1:1.1, the amount ratio of the precursor, deionized water and hydrazine hydrate is 1g:1000mL:10mL, and the mass fraction of hydrazine hydrate is 80%.

[0045] Embodiment 3: A method for preparing an antistatic PC composite material based on graphene, comprising the following steps:

[0046] Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 5 hours at a speed of 150 r / min and a temperature of 110° C. to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed uniformly, and the mixture is reacted for 5 hours at a speed of 200 r / min and a temperature of 90° C. to obtain modified silicone;

[0047] Step A2: Modified organosilicon, aniline and DMF were mixed, and reacted for 1.5 hours at a speed of 200 r / min, a temperature of 85° C. and a pH value of 12 to obtain a modified monomer. The modified monomer, 1,4-cyclohexanedimethanol, diphenyl carbonate, lithium acetylacetonate and 4-methylaminopyridine were protected by nitrogen and reacted for 3 hours at a temperature of 135° C. The temperature was raised to 210° C. and reacted for 6 hours to obtain a pretreated polycarbonate.

[0048] Step A3: The pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and DMF are mixed uniformly, stirred and hydrochloric acid is added to a pH value of 2 at a speed of 200 r / min and a temperature of 90°C, and ammonium persulfate is added to react for 25 hours to obtain a modified polycarbonate. The modified polycarbonate, modified filler and zinc oxide are added to a twin-screw extruder, and extruded and cooled at a speed of 80 r / min, a temperature of 240°C in the first zone, a temperature of 240°C in the second zone, a temperature of 245°C in the third zone, a temperature of 245°C in the fourth zone, a temperature of 245°C in the fifth zone and a temperature of 250°C in the sixth zone to obtain an antistatic PC composite material.

[0049] The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane described in step A1 is 2.4:2:3, the molar ratio of dihydrogenpolysiloxane and allyl alcohol glycidyl ether is 1:2, and the amount of chloroplatinic acid used is 1‰ of the mass of dihydrogenpolysiloxane.

[0050] The molar ratio of the modified silicone and aniline described in step A2 is 1:2, the molar ratio of the modified monomer, 1,4-cyclohexanedimethanol and diphenyl carbonate is 2.8:12:15, the amount of lithium acetylacetonate is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol, and the amount of 4-methylaminopyridine is 1‰ of the sum of the mass of the modified monomer and 1,4-cyclohexanedimethanol.

[0051] The amount ratio of the pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and ammonium persulfate described in step A3 is 20g:20mmol:2mmol:12mmol, and the mass ratio of the modified polycarbonate, the modified filler and zinc oxide is 100:30:3.

[0052] The modified filler is prepared by the following steps:

[0053] Step B1: adding concentrated sulfuric acid to a reactor, stirring and adding graphene and potassium permanganate at a speed of 1000 r / min and a temperature of 25° C., stirring for 4 h, heating to 50° C., reacting for 5 h, adding deionized water to terminate the reaction and washing to neutrality to obtain graphene oxide, mixing graphene oxide, ethylenediamine, dicyclohexylcarbodiimide and toluene, reacting for 3 h at a speed of 300 r / min and a temperature of 30° C., to obtain modified graphene;

[0054] Step B2: Furoyl chloride, 2,2-dihydroxymethylbutyric acid, triethylamine and toluene are mixed, and the mixture is reacted at a speed of 300 r / min and a temperature of 40°C for 5 hours, and the pH value is adjusted to be acidic to obtain an intermediate. The modified graphene, the intermediate, dicyclohexylcarbodiimide and DMF are mixed, and the mixture is reacted at a speed of 300 r / min and a temperature of 30°C for 3 hours to obtain a precursor. The precursor is dispersed in deionized water, hydrazine hydrate is added, and the mixture is reacted at a speed of 500 r / min and a temperature of 95°C for 25 hours to obtain a modified filler.

[0055] The amount ratio of concentrated sulfuric acid, graphene and potassium permanganate described in step B1 is 110mL:1g:6g, the mass fraction of concentrated sulfuric acid is 98%, and the molar ratio of carboxyl, ethylenediamine and dicyclohexylcarbodiimide on graphene oxide is 1:1:1.1.

[0056] The molar ratio of furanoyl chloride, 2,2-dihydroxymethylbutyric acid and triethylamine described in step B2 is 2:1:3, the molar ratio of the amino group, the intermediate and dicyclohexylcarbodiimide on the modified graphene is 1:1:1.1, the amount ratio of the precursor, deionized water and hydrazine hydrate is 1g:1000mL:10mL, and the mass fraction of hydrazine hydrate is 80%.

[0057] Comparative Example 1: Compared with Example 1, this comparative example uses graphene instead of the modified filler, and the other steps are the same.

[0058] Comparative Example 2: Compared with Example 1, no modified monomer was added to this comparative example, and the remaining steps were the same.

[0059] Comparative Example 3: Compared with Example 1, this comparative example uses pretreated polycarbonate instead of modified polycarbonate, and the other steps are the same.

[0060] The composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were made into 168 mm × 13 mm × 3.2 mm specimens according to ASTM D638, with a tensile speed of 50 mm / min, and the tensile strength was tested. According to ASTM D790, 127 mm × 12.7 mm × 3.2 mm specimens were made, with a test speed of 1.3 mm / min, and the bending performance was tested at a test temperature of -20°C. According to ASTM D257, the surface resistivity was tested. The test results are shown in Table 1 below.

[0061] Table 1

[0062]

[0063] It can be seen from the above table that the present invention has good mechanical strength and antistatic effect.

[0064] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an antistatic PC composite material based on graphene, characterized in that: The specific steps include: Step A1: octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain dihydrogenpolysiloxane; dihydrogenpolysiloxane, allyl alcohol glycidyl ether, chloroplatinic acid and DMF are mixed for reaction to obtain modified silicone; Step A2: mixing modified organosilicon, aniline and DMF, reacting to obtain a modified monomer, introducing nitrogen protection into the modified monomer, 1,4-cyclohexanedimethanol, diphenyl carbonate, lithium acetylacetonate and 4-methylaminopyridine, reacting to obtain a pretreated polycarbonate; Step A3: pretreated polycarbonate, aniline, N-(4-aminobenzene) maleimide and DMF are mixed and stirred, and hydrochloric acid and ammonium persulfate are added to react to obtain modified polycarbonate, and the modified polycarbonate, modified filler and zinc oxide are added to a twin-screw extruder, extruded and cooled to obtain an antistatic PC composite material; The modified filler is prepared by the following steps: Step B1: adding concentrated sulfuric acid to a reaction kettle, stirring and adding graphene and potassium permanganate, stirring, adding deionized water to terminate the reaction and washing to neutrality to obtain graphene oxide, mixing graphene oxide, ethylenediamine, dicyclohexylcarbodiimide and toluene to react, to obtain modified graphene; Step B2: After furanyl chloride, 2,2-dihydroxymethylbutyric acid, triethylamine and toluene are mixed and reacted, the pH value is adjusted to be acidic to obtain an intermediate, and the modified graphene, the intermediate, dicyclohexylcarbodiimide and DMF are mixed and reacted to obtain a precursor, and the precursor is dispersed in deionized water, hydrazine hydrate is added, and a reaction is carried out to obtain a modified filler.

2. The method for preparing a graphene-based antistatic PC composite material according to claim 1, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and tetramethyldisiloxane in step A1 is 2.4:2:3, and the molar ratio of dihydrogenpolysiloxane and allyl alcohol glycidyl ether is 1:

2.

3. The method for preparing a graphene-based antistatic PC composite material according to claim 1, characterized in that: The molar ratio of the modified silicone and aniline in step A2 is 1:2, and the molar ratio of the modified monomer, 1,4-cyclohexanedimethanol and diphenyl carbonate is 2.8:12:

15.

4. The method for preparing a graphene-based antistatic PC composite material according to claim 1, characterized in that: The amount ratio of the pretreated polycarbonate, aniline, N-(4-aminobenzene)maleimide and ammonium persulfate described in step A3 is 20g:20mmol:2mmol:12mmol, and the mass ratio of the modified polycarbonate, the modified filler and zinc oxide is 100:20-30:1-3.

5. The method for preparing a graphene-based antistatic PC composite material according to claim 1, characterized in that: The amount ratio of concentrated sulfuric acid, graphene and potassium permanganate described in step B1 is 110mL:1g:6g, and the molar ratio of carboxyl group, ethylenediamine and dicyclohexylcarbodiimide on graphene oxide is 1:1:1.

1.

6. The method for preparing a graphene-based antistatic PC composite material according to claim 1, characterized in that: The molar ratio of furanoyl chloride, 2,2-dihydroxymethylbutyric acid and triethylamine in step B2 is 2:1:3, the molar ratio of the amino group on the modified graphene, the intermediate and dicyclohexylcarbodiimide is 1:1:1.1, and the amount ratio of the precursor, deionized water and hydrazine hydrate is 1g:1000mL:10mL.

7. An antistatic PC composite material based on graphene, characterized in that: Prepared according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Light-color graphene conductive coating

    CN108774446A

  • Composite graphite sealing gasket and production process

    CN116694080A